The international and Hungarian situation and main tendencies of the egg production and consumption - Erdős, Adél Dorottya; Szőllősi, László (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
The egg is the cheapest animal protein that is considered as basic human nutritional goods. In addition, the egg is excellent functional food and it has also a role in health and prevention of diseases. The objective of the study is to introduce and to assess the international and Hungarian situation and main tendencies of table egg production and consumption. The egg production has doubled to 68.3 million tonnes between 1990 and 2013 in the world. Furthermore, the expected production will grow by 2% per year in the following two decades. At the same time, the annual egg consumption of the world has increased to 9.2 kg per person. The egg production of the EU was 7.6 million tonnes in 2015, which is more by 3.7% than in 2005 and further increase is expected. Contrary to the international tendency the layer flock and egg production have decreased dramatically by 30% between 2001-2016 in Hungary. Hungarian annual egg consumption was 214 pieces per person in 2013 which is lower by 45% than in 1990. At present the self-sufficiency rate of Hungary is between 70-75%. At the same time huge amount of eggs are imported into the domestic markets, which is resulted by competitiveness problems.